2005
DOI: 10.1258/1357633054893382
|View full text |Cite
|
Sign up to set email alerts
|

Prerecorded telemedicine

Abstract: In prerecorded telemedicine (also known as asynchronous or store-and-forward), the person sending the information and the person receiving it do not need to do so simultaneously; thus, viewing the information can be done at some later time. Prerecorded telemedicine is therefore not appropriate for emergency consultations. In prerecorded telemedicine systems, the following steps can be distinguished: (1) the acquisition of diagnostic information at the remote site; (2) its storage, which can be at either site, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 16 publications
(17 reference statements)
1
7
0
Order By: Relevance
“…In earlier reports, most people were enthusiastic about the introduction of telemedicine as a solution to bridging the gap between the city and remote areas [5][6][7][13][14][15] and this is also supported in this study as most of the respondents supported the use of e-health and telemedicine technology for patients care and would not mind its introduction into Nigeria health system. Definitely, the operation of the services will require that electricity supply, network coverage and other services improve tremendously for its effective implementation 1,21 .…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…In earlier reports, most people were enthusiastic about the introduction of telemedicine as a solution to bridging the gap between the city and remote areas [5][6][7][13][14][15] and this is also supported in this study as most of the respondents supported the use of e-health and telemedicine technology for patients care and would not mind its introduction into Nigeria health system. Definitely, the operation of the services will require that electricity supply, network coverage and other services improve tremendously for its effective implementation 1,21 .…”
Section: Discussionsupporting
confidence: 57%
“…It also includes electronic record of patients' registration and consultations (including provisional and definitive diagnosis and treatment) and health information system. The term is often used as an umbrella term that includes tele-health, telemedicine, electronic medical records, and other components of health information technology 7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed for educational purposes, some authors have deemed recordings equivalent to live lectures (Ambikairajah et al 2006(Ambikairajah et al , 2007, whereas others in the medical sector have suggested that recorded information should not be considered equivalent to live consultations (Della Mea 2005, Ng et al 2013, as they lack a necessary immediacy (Della Mea 2005). Nevertheless, such recorded information can serve as a form of preamble with the tracked consumer browsing of the information then serving as a basis upon which further interaction can be based (Ng et al 2013).…”
Section: Events Remote In Timementioning
confidence: 99%
“…Of major significance are the establishment of fast telephone lines starting with ISDN, the mass production of digital cameras, and the standardization of the open access network (internet) [4-6,8,10,11,14,19,22-26]. Based upon these three components several telemedicine systems have been constructed at the end of last century [7,8].…”
Section: History and Mile Stones Of Telemedicine/telepathologymentioning
confidence: 99%